2012
DOI: 10.1021/am300455d
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Asymmetric Supercapacitor Based on Graphene Hydrogel and Nanostructured MnO2

Abstract: We have successfully fabricated an asymmetric supercapacitor with high energy and power densities using graphene hydrogel (GH) with 3D interconnected pores as the negative electrode and vertically aligned MnO(2) nanoplates on nickel foam (MnO(2)-NF) as the positive electrode in a neutral aqueous Na(2)SO(4) electrolyte. Because of the desirable porous structure, high specific capacitance and rate capability of GH and MnO(2)-NF, complementary potential window of the two electrodes, and the elimination of polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
431
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 709 publications
(451 citation statements)
references
References 68 publications
12
431
3
1
Order By: Relevance
“…As seen from the CV curves (Fig. 4 a), the both electrodes exhibit nearly perfect symmetric rectangular shape which is indicative of ideal capacitors [1], however, there is a distinct difference between the current response in the CV spectra of other synthesis techniques that are available in the literature such as electrodeposition [34], hydrothermal autoclave [35], and reflux [36] for production of diverse Mn carbon based composites; the results obtained using the microwave approach are quite comparable and encouraging taking into account the reduced time for the synthesis of these materials by microwave. Fig.…”
Section: Electrochemical Characterisationmentioning
confidence: 93%
“…As seen from the CV curves (Fig. 4 a), the both electrodes exhibit nearly perfect symmetric rectangular shape which is indicative of ideal capacitors [1], however, there is a distinct difference between the current response in the CV spectra of other synthesis techniques that are available in the literature such as electrodeposition [34], hydrothermal autoclave [35], and reflux [36] for production of diverse Mn carbon based composites; the results obtained using the microwave approach are quite comparable and encouraging taking into account the reduced time for the synthesis of these materials by microwave. Fig.…”
Section: Electrochemical Characterisationmentioning
confidence: 93%
“…For example, Yong-Qing Zhao et al recently reported a composite of MnO 2 /graphene/nickel foam using a facile electrochemical deposition strategy [25]. Several studies have attempted to synthesize various graphene/MnO 2 nanocomposite using techniques such as chemical [26 27], microwave irradiation [28], electrodeposition [29][30][31], redox deposition [32] and polymer-assisted chemical reduction [33].…”
Section: Introductionmentioning
confidence: 99%
“…8 The energy density of supercapacitors can be enhanced by increasing their capacitance as well as their operating-potential window, which can be achieved more easily with asymmetric supercapacitors (ASCs) than with the symmetric supercapacitors (SSCs) since, with suitable combination of positive and negative electrode materials, the operational potential window as high as 2 V has been achieved even with aqueous electrolytes. 6,[9][10][11][12][13][14] In recent years, efforts have been expended to explore several ASCs with different electrode materials based on redox-active transition-metal oxides, like RuO 2 , 15 SnO 2 , 23 etc., which are not commercially viable owing to their high cost and environmental incompatibility. Accordingly, there is need to explore certain alternative combinations of positive and negative electrode materials to design a high-performance, cost-effective and environmentally benign ASC.…”
mentioning
confidence: 99%
“…4,[6][7][8][9][10][11]13,14,19,23,24 Besides MnO 2 suffers from poor electri- * Electrochemical Society Fellow. z E-mail: deb.sarkar1985@gmail.com; akshukla2006@gmail.com; sarma@iisc.ac.in cal conductivity (10 −5 -10 −6 S/cm), which affects the rate capability of the supercapacitors, but this limitation could be circumvented through nanostructured core-shell electrode design.…”
mentioning
confidence: 99%